Further records of pseudoscorpions (Arachnida, Pseudoscorpiones) from Saudi Arabia - Mahnert, Volker; Sharaf, Mostafa; Aldawood, Abdulrahman S. (Zootaxa, 2014)
Five species of pseudoscorpions are recorded from the southwestern mountains of the Kingdom of Saudi Arabia. Pseudochthonius arabicus Mahnert n. sp. is described as new to science; this genus was previously known only from sub-Saharan Africa and tropical South America and represents the first record of the family Chthoniidae from the Arabian Peninsula. Paratemnoides ellingseni (Beier, 1932), a widespread species in tropical Africa, and Withius piger (Simon, 1878) are added to the faunal list of Saudi Arabia. Minniza monticola Mahnert, 1991 and Rhacochelifer sonyae Mahnert, 1991 are apparently endemic to the southwestern mountains of Saudi Arabia.